Identification and Exclusion of Illegal Evidence in China: Past, Present and Future - Qi Yaping (Recent Research Advances in Arts and Social Studies Vol. 9, 2024)
The application of the exclusionary rule of illegal evidence in judicial practice is increasingly ignored in China. This is related to the failure to consolidate the foundation of illegal evidence. To identify and eliminate illegal evidence, three problems must be solved: the identification standard and basis of illegal evidence; The extent and scope of the exclusion of illegal evidence; and the Exclusion procedure of illegal evidence. In the process of establishing the exclusionary rule of illegal evidence in China, in order to avoid the complexity of the American exclusionary rule in the interpretation of rights, China consciously ignored the relationship between the exclusionary rule and constitutional rights, and tried to solve the above problems through specific document descriptions, but ignored the characteristics of the judge’s law that actually existed in the identification and exclusion of illegal evidence. This makes the judge’s duty to exclude evidence unclear, and the enthusiasm to exclude illegal evidence is not obvious.